Readers' preferences for print and online newspapers in North Western Nigeria : a study of daily trust - Isyaku Hassan
The general assumption is that print newspaper circulation will decline as the online editions are available for free. This study examined readers' preferences for print and online newspapers particularly in North Western Nigeria. Daily Trust being the largest circulating newspaper in the study area was selected as case study. The study employed mixed methods approach in which explanatory sequential design was used to collect and analyze data. Structured questionnaire was used to gather data from the reader ' perspective while interview questions were designed to determine the preferences from the newspaper management staff and experts in newspaper production. The questionnaire was administered to a randomly selected sample of 330 newspaper readers. The findings revealed a moderate (Mean=3.38) readers' pre erence for online newspaper to its print counterpart. A further analysis of the findings indicated that the decline in print newspaper circulation in the study area is related to proliferation of the internet and the introduction of online newspapers. It also indicated a high (Mean=3.77) overall motivation level of the readers towards reading online version of newspapers. The readers are motivated to read online newspapers because they provide timely updates. They also read online newspapers because they have access to the internet at cheaper rate; it allows them to follow the news better; it allows them to read the news quicker, and because of its accessibility, convenience and interactivity. The findings also revealed a moderate (Mean=3.36) level of readers' satisfaction, ith th contents of online newspapers. Meanwhile, majority (Mean=3. 51) of the readers were confident with the future of print newspapers despite the availability of the free online versions. The study concludes that the introduction of online newspapers may not lead to complete demise of the print versions. Therefore, newspaper publishers should strategize ways to fully embrace their technological fate.